The Strategy of Islamic Religious Teachers in Learning To Read The Students' Book with The Al-Miftah Lil Ulum Sidogiri Method - Vialinda Siswati; Achmad Fauzi; Sodikin Sodikin; Hurratul ‘In Mustafidah; Yusuf Suharto (Nazhruna: Jurnal Pendidikan Islam, 2022)
This study focused on: (1) How to plan the Al Miftah Lil Ulum Sidogiri Method in Learning to Read the Book of Santri at Madrasah Diniyah Syaichona Cholil Samarinda, (2) How to Implement the Al Miftah Lil Ulum Sidogiri Method in Learning to Read the Book of Santri at Madrasah Diniyah Syaichona Cholil Samarinda , (3) How to evaluate the Al Miftah Lil Ulum Sidogiri Method in Learning to Read the Book of Santri at Madrasah Diniyah Syaichona Cholil Samarinda. This study used a qualitative approach using the type of case study research. The data were collected by using interview techniques, field observations, and documentation. Furthermore, the data analysis techniques included (1) data reduction, (2) data display, (3) conclusions and verification. The results of this study the Al Miftah Lil Ulum Sidogiri Method in Learning to Read the Santri Book at Madrasah Diniyah Syaichona Cholil Samarinda, was carried out to find out the students' development and improvement in reading the yellow book (classic), and to find out what should be improved in the teaching and learning process.